ANALYSIS OF ACCOUNTING TREATMENT OF REJECT PRODUCTS IN DETERMINING COST OF PRODUCTION AT INSIL TAILORS BENGKULU CITY - Effendi, Yanto; Ramadhani, Desy; Herlin, Herlin (Perkumpulan Dosen Muda (PDM) Bengkulu, 2023)
The study aims to purpose of this research is to determine the extent of the analysis of accounting treatment of reject products in determining cost of production at Insil Tailors Bengkulu City. The result accounting treatment for reject products at Insil Tailors in Bengkulu City year 2022 is that they suffer a loss with 60 psc of amounting to IDR. 3,257,520. reject products found at Insil Tailors Bengkulu City are reject products that can be resold to increase income. Reject products occur as a result of employee negligence or sewing equipment that experiences problems or is reject, such as when the ironing process is too hot, improper cutting, and inappropriate measurements. The accounting treatment for reject products Insil Tailor Bengkulu City is by reselling the reject products at a price of Rp. 25,000/pcs.